045 Delivering continuous care to children and young people with learning disabilities in hospital: what does it mean for their parents?. (December 2018) - Oulton, K; Sell, D; Gibson, F
Abstract : Background: Children and young people with learning disabilities are frequent users of healthcare services, often receiving care in multiple settings, by many different teams, sometimes far from the family home. Hospitals, in particular, can be a challenging place for these children: they enter what may be an unfamiliar environment in which they are often exposed to complex information; painful and/or novel procedures; a loss of routine; confined spaces; excessive noise; excessive waiting; unfamiliar people; and a lack of appropriate communication channels. Parents play an important role in supporting their child through this experience. Whilst there is some evidence of parents describing being under-utilised or over-burdened by hospital staff, we know little of what it is like for them to be in hospital with their child and what their own needs are during this time. Methods: As part of a 12 month ethnographic study, we conducted multiple interviews with 12 parents of 9 children with learning disabilities and observed their journey as they accompanied their child to outpatient appointments and during in-patient stays. Key themes that emerged from the data, highlighted the importance parents placed on building a genuine partnership with professionals, as reflected by the acronym PARTNER: Preparation, Accessibility, Respect, Trust, Negotiation, Expertise, Reliability. Results: Researcher-voiced poems are used here to illustrate these findings, highlighting a consistent thread running through these poems of the need for good communication. Involving parents as partners in care helps them feel informed, involved, reassured and valued. Without this, parents can experience uncertainty, anxiety, frustration and anger, with the feeling of being expected to provide care rather than being a true partner.